The Influence of Socialization of SAK EMKM, Owner's Education Level, and Understanding of Accounting on the Implementation of SAK EMKM - Rieska Maharani; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
MSMEs in Indonesia have an essential role as pillars in economic development. However, MSMEs face problems related to financial management and difficulties in compiling financial records by applicable accounting standards. SAK EMKM is a financial accounting standard to support progress and make things easier for MSME players. Several factors can influence the implementation of SAK EMKM, namely socialization of SAK EMKM, the owner's education level, and understanding of accounting. The population in this research is MSME Culinary Tourism Centers (SWK), which are actively registered with the Surabaya City Cooperatives, SMEs, and Trade Office. The sampling technique used purposive sampling with the criteria of MSME actors who received SAK EMKM socialization and carried out financial records to obtain a sample size of 122 MSME actors. Data collection for this research used a questionnaire. The data analysis technique used is multiple linear regression analysis. Test data quality with validity and reliability tests. Next are the classical assumption tests: normality, multicollinearity, and heteroscedasticity. The hypothesis tests used were the t-test and F-test. The results of this research stated that the socialization of SAK EMKM and understanding of accounting partially had a positive and significant effect on the implementation of SAK EMKM. In contrast, the owner's education level had no significant effect on the implementation of SAK EMKM. This research shows that the socialization of SAK EMKM, the owner's education level, and understanding of accounting simultaneously have a positive and significant effect on the implementation of SAK EMKM.